The Role of Literature in Inculcating Moral Values among Students The Case of Third Year LMD English Students at Amar Telidji UniversityLaghouat-2017/2018 through The Old Man and the Sea - Horri, Fatima Zahra; Gasmi, Mustapha (Faculty of Letters and Foreign Languages Department of English, 2018)
It is clear that Literature is a significant subject to be studied since it reflects every single aspect of human life. In this thesis, the researcher investigates the role and power of literature in building and inculcating positive values among students. Novels and short stories are methods to communicate with different characters and events which are an effective way to teach values. The essential aim behind conducting this research is to show that literature is the authentic or best tool to teach moral values; Furthermore, the researcher investigates educational and moral values in Ernest Hemingway’s The Old Man and the Sea novella based on the analysis of the main character Santiago whose moral values no doubt leave a mark on every student. In this study, the researcher used descriptive research as an appropriate procedure to achieve this work. It describes the role of literature in teaching moral values. The quantitative approach is also used for collecting data through questionnaire administered to the third year LMD students. All data obtained from the questionnaire are analyzed, interpreted and represented in form of tables. The results show that literature can be helpful in reaching the highest levels of moral values. What is more, the present study provides some strategies to teach moral values through literature. As expected, literature is the best way to inculcate moral values among students